Digital Impressions for Fabrication of Definitive "All-on-Four" Restorations. Issue 1 (February 2015) - Gherlone, Enrico Felice; Ferrini, Francesco; Crespi, Roberto; Gastaldi, Giorgio; Capparé, Paolo
Abstract : Purpose: The aim of this study was to assess the accuracy of digital impressions for "all-on-four" implant rehabilitation. Materials and Methods: Patients edentulous in one or both jaws were randomly selected for this study. Complete arch immediately loaded prostheses supported by 4 implants (2 axial and 2 tilted) were placed. Five hours after implant placement, screw-retained full-arch temporary prostheses were positioned. After 4 months, a digital scan body was used to finalize definitive prosthesis. Radiographic assessments were obtained immediately after surgery and at each follow-up visit. Bone level measurements were reported at 6 and 12 months, and bone loss between upright and tilted implants was compared. Results: Fourteen definitive cast metal frameworks prosthesis were delivered to the patients. No implant dropout occurred. All prosthesis were screwed onto the dental implants, and x-ray examinations revealed a bar-implant connection accuracy. The implant survival rate was 100% for all positioned implants. No statistically significant differences ( P > 0.05) in crestal bone loss between tilted and upright implants were detected. Conclusions: Digital impression creates an accurate physical model significantly improving efficiencies for the dental team and streamlining the workflow.